The paradigm of questioning the world in research and teaching El paradigma del cuestionamiento del mundo en la investigación y en la enseñanza - Delgado, Tomás Ángel Sierra; Almouloud, Saddo Ag (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
EDITORIAL EM INGLÊS, ESPANHOL, fRANCÊS E pORTUGUÊS